PENDAPAT PARA FUQAHA’ TENTANG ZAKAT OBLIGASI DALAM KITAB HUKUM ZAKAT KARYA YUSUF QARDAWI - Amir Suud (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2013)
This article is the result of the research literature (library reseach) to answer the question of how the opinions of the jurists 'about the tithe bonds in the book of the law of charity work of Yu>suf Qardawi> and how Islamic legal review of the opinion of the jurists' about the tithe bonds in the book works of charity law Yu>suf Qardawi>. The results concluded that the opinions of the jurists' law of charity work in the book Yu>suf Qardawi> there are two opinions. The first opinion expressed by Sheikh Abd al-Rahma>n 'Isa> which holds that zakat is required if the bonds are bonds issued by companies engaged in trading, if the company is a pure industry then no zakat obligation. Second opinions expressed by Abu> Zahra, Abd al-Rahma>n Hasan, Abd al-Waha>b Khalaf who stated, that in accordance with the type of company bonds, which resulted in the company's bonds is different from other types of corporate bonds, but look at the bonds and gave him one of the types of laws anyway without seeing what the issuing company. In line with the above conclusion that a second opinion seems to be better than the first opinion in terms of the people (bondholders). Because basically every bondholder can find out how the value of its bonds and profit earned every year, and can easily pull out zakat.